A situated analysis of football goalkeepers' experiences in critical game situations - Villemain, A.; Hauw, D. (Perceptual and Motor Skills, 2014)
This study described elite football (soccer) goalkeepers' activity and performance in critical game situations. The 11 best French players (M age = 15.5 yr., SD = 0.5) participated in the study. Interviews focused on goalkeepers' experiences were conducted to identify meaningful events involved in failed actions. Players formulated 23 critical game situations. Verbatim encoding using a thematic analysis indicated that four main categories (coming off the line, goal-line clearance, one-on-one, and diving) represented the most critical situations encountered during matches. The relations among experience and action, inner states, background, attention contents, and intentions were elucidated. The discussion is grounded on the properties of such critical game situations and their implications for improving goalkeepers' performance.